Effects of Wheat Water-extractable Arabinoxylanon on the Processing Properties of Rice Flour and Eating Quality of Fresh Rice Noodles - Jiayang LI; Xinyuan WANG; Lijun YIN; Zhigang LIU; Xin JIA (Shipin gongye ke-ji)
To improve the problems of fresh rice noodles such as being prone to aging and eating quality declined during storage, the effects of wheat water-extractable arabinoxylan (WEAX) addition (0%~1.0%, w/w) on the gelatinization and thermodynamic properties of rice flour, as well as the color, cooking, texture and aging properties of fresh rice noodles were systematically studied. The results showed that compared with the blank control group, the gelatinization viscosity of rice flour with WEAX increased from 3454.00 cP to 3773.65 cP, and the gelatinization enthalpy value decreased from 4.02 J/g to 3.18 J/g. WEAX with different additive amounts had no significantly effect on gelatinization temperature of rice flour-WEAX mixed systems (P>0.05). The breakage rate and the cooking loss of fresh rice noodles with 0.6% WEAX reached the minimum of 11.46% and 8.48%, respectively. As the increase of WEAX addition, the color and texture quality of fresh rice noodles were significantly improved (P<0.05). Compared with the original rice noodles, the aging degree, relative crystallinity and infrared peak intensity ratio R1047/1022 of fresh rice noodles with 1% WEAX after aging for 7 days decreased by 67.3%, 71.4% and 30.9%, respectively. In summary, the addition of 1% WEAX could improve the color and texture quality of fresh rice noodles and delay the long-term aging process of rice noodles. This study will provide a theoretical basis for expanding the application of WEAX in the starch food industry and improving the quality of starch food.